Marine Toxins and Nociception: Potential Therapeutic Use in the Treatment of Visceral Pain Associated with Gastrointestinal Disorders - Andreina Baj; Michela Bistoletti; Annalisa Bosi; Elisabetta Moro; Cristina Giaroni; Francesca Crema (Toxins, 2019)
Visceral pain, of which the pathogenic basis is currently largely unknown, is a hallmark symptom of both functional disorders, such as irritable bowel syndrome, and inflammatory bowel disease. Intrinsic sensory neurons in the enteric nervous system and afferent sensory neurons of the dorsal root ganglia, connecting with the central nervous system, represent the primary neuronal pathways transducing gut visceral pain. Current pharmacological therapies have several limitations, owing to their partial efficacy and the generation of severe adverse effects. Numerous cellular targets of visceral nociception have been recognized, including, among others, channels (i.e., voltage-gated sodium channels, VGSCs, voltage-gated calcium channels, VGCCs, Transient Receptor Potential, TRP, and Acid-sensing ion channels, ASICs) and neurotransmitter pathways (i.e., GABAergic pathways), which represent attractive targets for the discovery of novel drugs. Natural biologically active compounds, such as marine toxins, able to bind with high affinity and selectivity to different visceral pain molecular mediators, may represent a useful tool (1) to improve our knowledge of the physiological and pathological relevance of each nociceptive target, and (2) to discover therapeutically valuable molecules. In this review we report the most recent literature describing the effects of marine toxin on gastrointestinal visceral pain pathways and the possible clinical implications in the treatment of chronic pain associated with gut diseases.